Piezoelectric properties of low temperature sintering in Pb(Zr,Ti)O3-Pb(Zn,Ni)1/3Nb2/3O3 ceramics for piezoelectric transformer applications - A. Ngamjarurojana (2018)
In this study, in order to develop low-temperature sintering ceramics for a multilayer piezoelectric transformer application, we explored CuO and Bi2O3 as sintering aids at low temperature (900 °C) sintering condition for Sb, Li and Mn-substituted 0.8Pb(Zr0.48Ti0.52)O3-0.16Pb(Zn1/3Nb2/3)O3-0.04Pb(Ni1/3Nb2/3)O3 ceramics. These substituted ceramics have excellent piezoelectric and dielectric properties such as d33 ∼ 347 pC/N, kp ∼ 0.57 and Qm ∼ 1469 when sintered at 1200 °C. The addition of CuO decreased the sintering temperature through the formation of a liquid phase. However, the piezoelectric properties of the CuO-added ceramics sintered below 900 °C were lower than the desired values. The additional Bi2O3 resulted in a significant improvement in the piezoelectric properties. The composition Sb, Li and Mn-substituted 0.8Pb(Zr0.48Ti0.52)O3-0.16Pb(Zn1/3Nb2/3)O3-0.04Pb(Ni1/3Nb2/3)O3 + 0.5 wt% CuO + 0.5 wt% Bi2O3 showed the value of kp = 0.56, Qm = 1042 (planar mode), d33 = 350 pC/N, when it was sintered at 900 °C for 2 h. These values indicated that the newly developed composition might be suitable for multilayer piezoelectric transformer application. © 2007 Elsevier Ltd and Techna Group S.r.l.